The Form of Dispute Settlement in The Border of Sea Region of Asean State Members and Its Implications to Indonesia - Delfiyanti, Delfiyanti (Andalas International Journal of Socio-Humanities, 2020)
The ASEAN Charter itself has been recently effective on 15th December 2008 after going through the ratification of the ASEAN state members that have ratified a charter that makes the regional bloc into an "legal" institution (Legal Personality) for the first time. As we know the relationship among ten ASEAN state members does not always work smoothly. Sometimes disputes arise also where the most frequently occurring case is concerned to the regional border or annexation of Malaysia-Singapore about the regional annexation of Batu Pateh, Thailand-Cambodia border as a seizure and the other border areas. Particularly in the sea region a dispute is often occurred among ASEAN state members since at some certain marine areas it is still not yet clear about the borders of its territory. This has resulted in overlapping claims among these countries. It influences the fishing areas where the fishing boats and fishermen would be considered illegal fishing when crossing the boundaries of sea claimed by a country. Though the sea areas are not yet clear about the ownership. Eventually it became a dispute among ASEAN state members. Hence, it takes ways of resolving disputes among ASEAN state members. In this case, the ASEAN Charter contains the methods for settling disputes among ASEAN state members. Indonesia itself is one of ASEAN state members which has sea border with some ASEAN state members which also have sea dispute. Therefore, Indonesia also participated and signed the agreement and will also be bound at later by the ways set out in the ASEAN Charter.